If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3n + -4 = -11 Reorder the terms: -4 + 3n = -11 Solving -4 + 3n = -11 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 3n = -11 + 4 Combine like terms: -4 + 4 = 0 0 + 3n = -11 + 4 3n = -11 + 4 Combine like terms: -11 + 4 = -7 3n = -7 Divide each side by '3'. n = -2.333333333 Simplifying n = -2.333333333
| Xy-3x=30 | | 9u+10=4u-20 | | 6=-6u+3(u+2) | | y=0.7+1 | | 4w+16-6w=2 | | -63=7x-28 | | x+0.1x=600000 | | 4v-32-6v=-22 | | -6x(x+12)=0 | | -3a-9=-21 | | -2w=20 | | -12x-6=-42 | | x(3)+2x(2)-x-2=0 | | (-5b^6)-(8b^4+14)= | | 5(2x)(x)+152=0 | | 3(j-5)+3=9 | | 27x^3+9x^2=0 | | -4p-(-19p)-(-11p)-(-15)=-11 | | 5*(2x+3x)=8x-6 | | 4x-5=3x+2x | | X=16-2x | | 11p-5p-17=36 | | 12z-7z=5 | | 18w+-6w+-16=20 | | 6c-c+5c=20 | | 7x^2-12x-8=-4 | | 3x+y=26fory | | 3(w-7)+5=8 | | (8r-3)-(-7r+1)=-6 | | 3c+6c+25=-2 | | 2(4*6)+13= | | 2(3t-1)=6-t |